Operable abstraction: how toys changed the logic of modern sculpture. (2019) - Stott, Timothy
Abstract : In The World as Sculpture of 1999, James Hall declared that 'Throughout the century, homo faber has merged with homo ludens, and the artist's studio has been a combination of workshop and playroom', to the point that, since the late 1960s, 'it has become a cliché of criticism to compare works of contemporary art to toys'. Behind this cliché, we find that twentieth-century artists have explored the plastic, pedagogical, fictive and interactive properties of toys in quasi-cultic and fantasy objects, dolls and puppets, kits and games, interactive devices and playground equipment. On the one hand, because children and their playthings are future-oriented, protean, sometimes spontaneous, they have featured in many artists' visions of a new art and, at times, a new world. On the other hand, toys conjure something older and darker, and persist into the present as what British ethnologist Edward Tylor called survivals or residues. This essay introduces the special issue by showing how the encounter with toys expanded the logic of sculpture into 'operable abstraction', thus transforming how, where and by whom sculptures were made, displayed and encountered.